The Mindanao State University Darangan Cultural Troupe a historical and descriptive study - Ele, Henrietta Hofer 1935- (s.n.], 1974)
The primary purpose of this study is to trace the historical organization and development of the Mindanao State University Darangan Cultural Troupe and evaluate its role as an implementing arm of the University's objective to "hasten national integration between the cultural minorities of the Philippines and dominant Christian population".